The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4103/0028-3886.63791
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of intracranial aneurysms previously treated with endovascular therapy

Abstract: Endovascular treatment with coils of cerebral aneurysm is being increasingly used for definitive treatment. An increasing number of patients are coming for surgical intervention either for recurrences, incomplete coil embolization or its complications. Our objective was to assess the surgical management in such patients. This was a retrospective analysis of the patients who were initially treated with endovascular embolization and later managed surgically with clipping either for unsuccessful coiling, recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Over the last two decades, several series have detailed techniques, results, and complications of surgery for previously coiled aneurysms [5,10,11,21,26,30,36]. However, most of these series are small [6,7,13,16,21,34] and it is difficult to have an overall sense of the complications and outcomes for treatment of previously coiled aneurysms. We conducted a systematic review of the literature to evaluate the safety and efficacy of surgical treatment of previously coiled aneurysms analyzing outcomes by aneurysm rupture status, location, timing of treatment and type of surgical therapy.…”
Section: Introductionmentioning
confidence: 97%
“…Over the last two decades, several series have detailed techniques, results, and complications of surgery for previously coiled aneurysms [5,10,11,21,26,30,36]. However, most of these series are small [6,7,13,16,21,34] and it is difficult to have an overall sense of the complications and outcomes for treatment of previously coiled aneurysms. We conducted a systematic review of the literature to evaluate the safety and efficacy of surgical treatment of previously coiled aneurysms analyzing outcomes by aneurysm rupture status, location, timing of treatment and type of surgical therapy.…”
Section: Introductionmentioning
confidence: 97%
“…We decided finally to adopt a combined strategy that would keep the vascularization during the entire procedure. In the literature, a combined treatment approach for the same aneurysm has been described in the following different situations: (i) Delayed endovascular[ 2 4 17 ] or surgical treatment[ 2 15 17 19 33 ] after previously unsuccessful surgical or endovascular treatment; (ii) temporary endovascular parent artery occlusion during clipping,[ 27 42 43 46 ] and (iii) microsurgical revascularization followed by endovascular parent artery occlusion and flow-redirection techniques. [ 9 17 30 ] In our experience,[ 42 ] we have previously treated a series of eight giant paraclinoid and four vertebro-basilar aneurysms in combination with the neuroradiologist, where an adequate flow allowed a temporary occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…There have been isolated reports in the literature undermining the importance of coil extrusion, migration and mass effect of coil extrusion, migration and mass effect Kumar et al 22 have reported five ruptured aneurysms that were clipped after an unsuccessful EVT. One MCA aneurysm ruptured during coiling, leading to abandonment of the procedure.…”
Section: Extrusion Migration and Mass Effect: The Coil Effect?mentioning
confidence: 98%